2006
DOI: 10.1002/jgm.939
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus (AAV) serotypes 2, 4 and 5 display similar transduction profiles and penetrate solid tumor tissue in models of human glioma

Abstract: In addition to the widely used AAV2 serotype, AAV4 and AAV5 serotypes may also be used to transduce biologically diverse glioma cell lines. They also penetrate and transduce solid human tumor tissue derived from patient biopsies. Therefore, the data presented here provide a proof of principle for developing AAV4 and AAV5 as treatment vehicles for human malignant gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…20 Direct transplantation of such 'organotypic' spheroids into rodent brains forms lesions that eventually recapitulate all the histopathological hallmarks of GBM in situ, such as extensive single-cell infiltration, angiogenesis the occurrence of necroses with palisading tumor cells, endothelial proliferations and dilated, thrombotic vessels. 18,21 We have recently used this model to evaluate gene transfer to human GBM cells 22,23 as well as to study the biological aspects of tumor cell invasion. 24 Since the described model reflects the key features of human glioma progression, we chose to assess the effect of G207 on a set of xenograft phenotypes that follow these biological features.…”
Section: Introductionmentioning
confidence: 99%
“…20 Direct transplantation of such 'organotypic' spheroids into rodent brains forms lesions that eventually recapitulate all the histopathological hallmarks of GBM in situ, such as extensive single-cell infiltration, angiogenesis the occurrence of necroses with palisading tumor cells, endothelial proliferations and dilated, thrombotic vessels. 18,21 We have recently used this model to evaluate gene transfer to human GBM cells 22,23 as well as to study the biological aspects of tumor cell invasion. 24 Since the described model reflects the key features of human glioma progression, we chose to assess the effect of G207 on a set of xenograft phenotypes that follow these biological features.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, significant progress in virology may come to help: researchers are currently studying novel gene delivery methods and in this context recombinant adenoassociated viruses may serve as low immunogenic and cellor tissue-specific vectors. Already the proof of the principle has been delivered in experiments with adeno-associated viruses which penetrate solid tumor tissue [122] and it is to be expected that these tailored viruses can be used as a platform for advanced drug and imaging nanotechnology [123]. Furthermore, double action can be achieved by combining oncolytic viruses with preferential replication in tumor cells with drug containing nanoparticles [124].…”
Section: Antibody-based Targetingmentioning
confidence: 99%
“…AAV2 has been the most widely used AAV serotype for gene delivery to the CNS, transducing almost exclusively neurons in different brain structures [175-178], and supporting long-term transgene expression in the CNS [179-181] as well as in the dorsal root ganglia [182]. AAV2 has shown higher transduction efficiency in glioblastoma in vitro and in vivo when compared to serotypes 4 and 5 [183]. However, other studies have demonstrated a higher distribution and transduction in the CNS when using rAAV serotypes 1 and 5 [175, 184, 185].…”
Section: Aav Based Vectorsmentioning
confidence: 99%
“…However, other studies have demonstrated a higher distribution and transduction in the CNS when using rAAV serotypes 1 and 5 [175, 184, 185]. The different AAV serotypes have been exploited on their ability to efficiently transduce distinct regions of the brain due to different cellular tropisms [174, 183, 186]. …”
Section: Aav Based Vectorsmentioning
confidence: 99%